Sharing Knowledge Between Academia and The Industry: Audiovisual Translation and Accessibility Research for Practice - Tuominen, Tiina; Silvester, Hannah (Journal of Audiovisual Translation, 2021)
Audiovisual translation and accessibility research have huge potential to transform and improve the work of practitioners in these areas. However, research publications are not necessarily designed to address the practical implications of research, or to be accessible to practitioners outside academia. This special issue is for practitioners, and it aims to demonstrate how research can be useful to them. The research projects presented in the articles serve practical purposes in a variety of ways, from proposing analytical models to aid in selecting translation strategies, to exploring developments in working practices. Vibrant collaboration between all stakeholders in AVT and accessibility could bring benefits to both research and practice. This introduction discusses some of the challenges involved in making such exchanges happen and examines how those challenges could be overcome.